إستراتيجيات تخفيف أثر الصدمات على أسواق المال "دراسة حالة " - وحيدة ملاوحية; خولة طار (My University, 2021)
The recurrence of financial crises in European and Arab countries, during the nineties, constituted an interesting and interesting phenomenon, and the reasons for this were because their negative effects were severe and dangerous, threatening economic and political stability, which affects in particular the global and Arab financial markets, which have a key role in the economy, despite the multi Forms and types of crises, but the goal of confronting them is to reduce deterioration and losses and to benefit from the emerging situation in reform and development, how much appropriate measures or strategies can be taken to prevent its recurrence. Among the most important reasons that prompted us to choose this topic is to feel the value and importance of the topic in light of the rapid global transformations, and its importance lies in strategies that work to mitigate the impact of crises on global financial markets and corporate governance on financial markets in general and emerging markets in particular, because the good application of governance Increases efficiency and reduces falling into crises, as well as increasing efficiency in financing the economy. To give more value to our study, we have studied the most important global and emerging stock exchanges "Shanghai Stock Exchange, Egypt Stock Exchange, Amman Stock Exchange", as an applied study, and we reached the following results: These stock exchanges have been affected by their indicators by the deterioration of the economy, which in turn was affected by the Corona pandemic, and we also noticed the lack of efficiency in these stock exchanges and the lack of good application of governance principles ................................................................... تشكل تكرار الأزمات المالية في الدول الأوروبية والعربية، خلال التسعينات ظاهرة مثيرة والاهتمام، ويرجع أسباب ذلك غلى أن آثارها السلبية كانت حادة وخطيرة هددت الاستقرار الاقتصادي والسياسي مما يؤثر بشكل خاص في الأسواق المالية العالمية والعربية، التي لها دور أساسي في الاقتصاد، وعلى الرغم من تعدد أشكال الأزمات وأنواعها إلا أن الهدف من مواجهتها يتمثل في الحد من التدهور والخسائر والاستفادة من الموقف المستجد في الإصلاح والتطوير، كم يمكن اتخاذ الإجراءات أو الإستراتيجيات الملائمة لمنع تكرارها. ومن بين أهم الأسباب التي دفعت بنا لاختيار هذا الموضوع هو الشعور بقيمة وأهمية الموضوع في ظل التحولات المتسارعة العالمية، وتكمن أهميته في الإستراتيجيات التي تعمل على تخفيف أثر الأزمات على الأسواق المالية العالمية وحوكمة المؤسسات على الأسواق المالية بصفة عامة والناشئة بصفة خاصة، لأن التطبيق الجيد للحوكمة يزيد من الكفاءة ويقلل من الوقوع في الأزمات وكذلك تزيد الكفاءة في تمويل الاقتصاد. ولإعطاء قيمة أكثر لدراستنا قمنا بدراسة أهم البورصات العالمية والناشئة "بورصة شنغهاي، بورصة مصر، بورصة عمان"، كدراسة تطبيقية وتوصلنا فيها للنتائج التالية: أن هذه البورصات قد تأثرت مؤشراتها بتدهور الاقتصاد والذي بدوره أثرت عليه جائحة كورونا، كما لاحظنا غياب الكفاءة في هذه البورصات وعدم التطبيق الجيد لمبادئ الحوكمة .